Sistem Informasi Pengaduan Gangguan PDAM Tanah Laut Berbasis Web - Alivia Agiesta Novitasari; Wan Yuliyanti (Teknik Informatika, Politeknik Negeri Tanah Laut, 2019)
Tanah Laut Regional Water Supply Company (PDAM) is engaged in the management and sales of drinking water services with about 7,848 customers which spread throughout Tanah Laut Regency. Complaints of interference carried out by the customer manually to the customer relations department by coming directly to the office of the Tanah Laut PDAM which will then be distributed to the technical and distribution transmission. Based on these problems, a web-based PDAM Tanah Laut PDAM complaint information system is built that can make it easier for customers to make complaints of disturbances and to make it easier for officers to distribute it. This can produce accurate and efficient complaints data. This web-based information system for complaints of disturbance at PDAM Tanah Laut is built with programming languages PHP, HTML, CSS and JavaScript. And designed using Entity Relationship Diagrams and Data Flow Diagrams. The results of blackbox testing show that the functionalities of the system are perform properly.